The Relationship Between Cancer Stage And Quality Of Life In Cancer Patients - Setyaningsih, Vita; Prasestiyo, Hamudi; Wantonoro, Wantonoro (Universitas 'Aisyiyah Yogyakarta, 2026)
Cancer transcends physical pathology, manifesting as a chronic condition that imposes profound psychological, social, and spiritual burdens, often compromising the patient's quality of life (QoL). Recognizing that disease progression is a potential predictor of this decline, this study aims to analyze the correlation between cancer staging and quality of life. Conducted at PKU Muhammadiyah Gamping Hospital using an observational cross-sectional design, the study involved 75 cancer patients recruited via purposive sampling based on Slovin’s formula. Cancer staging data were validated through medical records and interviews, while QoL was assessed using the EORTC QLQ-C30 instrument. Data analysis using the Spearman Rank correlation test revealed that the majority of respondents presented with advanced-stage cancer and reported moderate-to-low QoL. A significant correlation was found (p-value 0,001), indicating an inverse relationship where advanced cancer stages are associated with lower quality of life. These findings underscore the urgency of early detection and comprehensive symptom management, including the optimization of palliative care. Consequently, this study recommends the integration of routine QoL assessments into clinical practice and the reinforcement of the nurse's role in the holistic management of cancer patients.